NILAI PENDIDIKAN KARAKTER DALAM BUKU MATA PELAJARAN BAHASA INDONESIA SEKOLAH DASAR - Fikan Hardy Firmansyah; Ema Zahra Salsabila; Retno Anjarwati; Rahma Inka Ariani; Alfi Khoiru An Nisa (Al-ATHFAL: Jurnal Pendidikan Anak, 2026)
Character education plays an important role in shaping and developing the attitudes and behaviors of elementary school students. Indonesian language learning is one of the strategic means of instilling character values because it is directly related to the development of attitudes, language, and culture. Therefore, this study aims to describe and integrate the implementation of character education through Indonesian language lessons in elementary schools. The method used in this study is descriptive qualitative. The data collection technique is note-taking. The data analysis technique uses content analysis with a qualitative approach. The results of this study indicate that character values can be effectively instilled through dialogue and reading texts used in learning, including the values of empathy, social awareness, sharing, responsibility, discipline, tolerance, obedience to rules, concern for the environment, cooperation, mutual assistance, and leadership. These values are presented contextually through storylines and learning activities that are close to the lives of students, so that Indonesian language learning not only serves to improve language skills but also acts as a strategic means of character building for elementary school students.